Kontribusi Minat Belajar, Lingkungan Dan KemandirianBelajar Terhadap Hasil Belajar Matematika Siswa KelasX SMK Muhammadiyah Delanggu Tahun Ajaran 2014/2015 - Pramanasari, Nurbaity Eka, Prof. Dr. Sutama, M.Pd (2015)
The purpose of this study to examine the contribution of interest, the environment, and independent learning on learning outcomes of math class X SMK Muhammadiyah Delanggu. This study used quantitative research methods with descriptive correlational design. The population in this study were all students of class X number of 232 students with a sample of 147 students is determined by the formula Slovin. The sampling technique using proportional random sampling drawn randomly. The technique of collecting data using questionnaires and documentation. Questionnaire technique is used to obtain the data of interest, the environment, and independent learning. The questionnaire used in the study was tested to determine the validity and reliability of the questionnaire. Documentation techniques used to obtain the data result of learning mathematics. Data were analyzed using multiple linear regression analysis to test the hypothesis prerequisites include normality test, linearity, and multicollinearity test. Based on data analysis and discussion of this study concluded that there is a contribution of interest, the environment, and independent learning on learning outcomes of math class X SMK Muhammadiyah Delanggu either simultaneously or partially, the direction of regression coefficients for F = 15.254, the effective contribution of 24.2%. The effective contribution of each predictor is contributing 7.7% interest in learning, learning environment contributes 10.17% and 6.37% contribution to independent learning.